Motorcycle officers of Eastern Washington : and relevant crime stories - Bamonte, Tony, 1942- (Tornado Creek Publications, 2018)
"Eastern Washington has been served by motorcycle officers since 1910. The authors each served in that capacity during the late 1960s to early 1980s and found it to be a memorable and stimulating police experience. This book features motorcycle officers from the Spokane Police Department, the Spokane County Sheriff's Office, and the Washington State Patrol. During their service on motor or other in other capacities, they investigated literally thousands of incidents, some tragic, and some the most dreadful and ghastly crimes ever committed in Washington State. Their stories offer first hand perspectives revealing both the crimes and how they were solved. This book also covers the nation's oldest active murder case with numerous and previously unpublished photographs, about which the book "Breaking Blue" by Timothy Egan was written."-- back cover